Pengaruh Citra Destinasi Di Media Sosial Terhadap Minat Kunjungan Destinasi Ekowisata Hutan Mycelia Lembang - Dianova, Hanifa; Pamungkas, Adinda Putri; Azzahra, Galis; Aqidah, Shinta Wangi; Devi, Syailla Azka Trifania; Khaerani, Rijal (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p09, 2024)
Ecotourism destinations are increasingly numerous and diverse in the current era. This is a phenomenon caused by the increased development of sustainable tourism. Promotion and introduction of ecotourism destinations is also increasing and diverse, a relevant example is promotion using social media. The depiction of a tourist spot contained in social media is one of the several things that tourists focus on when looking for this information. However, not all tourists pay attention to this, this is the initial foundation concerning this study which seeks to identify the effect of the image regarding said tourist destinations on social media on visit interest, especially its impact on the tourist’s interest in visiting ecotourism destinations. The method used relates to the concept of Tourist Perceived Value and the influence of E-WOM. The results of this study show that 68% of people was able to find the information about Hutan Mycelia through social media and 41% was influenced to visit the place. The conclusions obtained shows that the image of tourist attractions on social media is influential on interest in visiting tourist destinations. However, it is highly recommended to conduct further research on tourist visit interest itself. Keywords: ecotourism; destination image; social media; tourist visit interest